ADAPTING TEXTBOOK ACTIVITIES FOR INCREASING CLASSROOM INTERACTION (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
In this article adapting textbook activities for increasing students interaction is being discussed with the examples from English classroom.